Analisis Mutu Pelayanan Terhadap Kepuasan Pasien Di Instalasi Gawat Darurat Rumah Sakit Umum Daerah Dr. Pirngadi Kota Medan - Octaria Novita, Arifah Devi Fitriani, Nur’aini (Journal of Health and Medical Science, 2022)
Hospital services as one of the service sectors that play an important role. Based on the results of direct interviews, 56.6% of patients were dissatisfied with the services provided at the Emergency Installation of the Regional General. The purpose of this study was to determine the effect of service quality on patient satisfaction in the Emergency Installation of Dr. General Hospital. Pirngadi Medan City. The research design used in this study was an analytic survey with a cross sectional approach. The population in this study were 10,730 patients and the sample was taken by accidental sampling, which was 100 people. Data collection methods are primary data and secondary data. Analysis of the data used is a binary logistic regression test. The results of the efficiency study had a sig-p value of 0.023 < 0.05, a sig-p value of 0.044 < 0.05, sig-p comfort 0.031 < 0.05 and service continuity sig-p 0.032 < 0.05. The conclusion in this study is that there is an effect of efficiency, human relations, comfort and continuity of service on patient satisfaction. Suggestions for hospitals are expected to be able to better understand the importance of service quality in accordance with the regulations of the ministry of health and professional code of ethics in providing health services to patients to the maximum, through increasing the professionalism of health workers, efficiency, security, satisfaction and facilities in hospitals.